A series of new lanthanoid thioarsenates: insights into the influence of lanthanide contraction on the formation of new lanthanoid thioarsenates1. Issue 16 (28th April 2015) - Zhou, Jian; Zhao, Rong-Qing; Yang, Tao; Liu, Xing; Xiao, Hong-Ping; Zou, Hua-Hong; Tan, Xiao-Feng
<x xml:space="preserve">Abstract</x> A series of new lanthanoid thioarsenates were prepared and they would be helpful for gaining insights into the influence of lanthanide contraction on the formation of other new lanthanoid thioarsenates.